"What Does It Matter How We Define It?": Exploring Definitions of DMST Among Service Providers and Victims/Survivors. Issue 2 (3rd April 2019) - O'Brien, Jennifer E.
ABSTRACT: Domestic minor sex trafficking (DMST) is one of the most prevalent yet hidden forms of child abuse in the United States. DMST victims are diverse in age, race, and socioeconomic status. Many DMST victims are involved in state-level systems including the child welfare and/or juvenile justice system. State-level systems are federally mandated to identify children who are at risk or survivors of DMST. Unfortunately, DMST victim/survivor identification is inconsistent and often ineffective and is based on service providers' and DMST victims'/survivors' de facto definitions of DMST. This study presents exploratory, qualitative findings regarding service provider and DMST victim/survivor de facto definitions of DMST. In addition, it explores how these definitions are different from and/or similar to extant federal and state legal definitions. Content analysis revealed three key qualitative themes, including force/fraud/coercion, commercialization, and DMST as a form of child sexual abuse. Importantly, DMST victim/survivor and service provider definitions of DMST are different, which may be contributing to ineffective DMST victim/survivor identification protocols. Furthermore, there are several important differences between participants' definitions of DMST and extant federal and state legal definitions. Implications for policy and practice are discussed.